Advancing practical applications of resilience in Aotearoa-New Zealand - David Wither (Resilience Alliance, 2021)
Resilience is increasingly used to inform natural hazard risk management. From global to national to local levels of governance and decision making, resilience concepts are becoming institutionalized and operationalized in both public and private domains. However, as these ideas have shifted from their origins in ecology and been adopted by other disciplines, policy makers, and practitioners, key insights from the initial ecological conceptualization have been left behind. The resulting gap between resilience as originally theorized and its current implementation gives rise to several interconnected challenges: (i) loss of nuance in the meaning of the concept due to rapid adoption, which leads to: (ii) an inability to adequately account for normative or qualitative aspects of social theory, and: (iii) the problem of measurement. Key factors associated with resilience are intangible (difficult to objectively measure) and public bureaucracies are reliant upon objective measurement, i.e., targets and indicators, to operationalize policies. Multi-capital frameworks have been advanced as a potential solution to the problem of measurement in the literature. In this paper, we critically analyze how the concepts of social and human capital can be used to address these challenges and account for intangible sources of value. Drawing on a case study of complex multi-hazards in rural Aotearoa-New Zealand (NZ), as well as the NZ government's Living Standards Framework (a multi-capital framework) we highlight the importance of addressing these challenges to adequately realize the benefits of resilience and identify the successes and limitations of this approach. Results provide insight into the interlinked nature of the challenges and the importance of reconciling resilience theory and praxis. Findings also demonstrate the potential ways in which a combination of resilience thinking and multi-capital frameworks can add value to decision-making structures within public bureaucracies, the private sector, and academia.